PENGARUH TINGKAT PENDIDIKAN DAN TINGKAT UPAH TERHADAP PRODUKTIVITAS TENAGA KERJA DI KALIMANTAN BARAT. - Aresty, Novel; Nuraini, Nuraini; Budiman, Jumardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The purpose of this study is to empirically investigate the effect of acculturation and wages on labor productivity in West Kalimantan. The panel data regression method (pooled data) was used as the analytical method in the quantitative research. Secondary data obtained from the central statistics agency (BPS) for the last 5 years, namely the period 2017-2021, was used in this study. The study's findings indicate that education has a positive and significant effect on labor productivity, whereas wage has no effect on labor productivity. The two independent variables then have a significant effect on labor productivity at the same time, with a coefficient of detemination of 10,57%.